Promoter demethylation of cerebellin 2 by ten-eleven translocation 3 contributes to peripheral sensitization in trigeminal neuropathic pain of mice - Xin-Ying Guan; Bao-Tong Yuan; Meng-Na Li; Tian Wang; Lin-Peng Zhu; Si-Yuan Song; Lu-Lu Ji; Yong-Jing Gao; Ling-Jie Ma (The Journal of Headache and Pain)
Abstract Background Chronic neuropathic pain involves complex molecular adaptations, and emerging evidence indicates that cerebellins (CBLNs) play a role in sensory processing. This study investigates the role of CBLN2 in trigeminal neuropathic pain (TNP) and examines its regulation through epigenetic mechanisms. Methods Bioinformatics analyses of CBLNs were performed using publicly available expression data from the trigeminal ganglion (TG). A mouse model of TNP was established through partial infraorbital nerve transection (pIONT). Facial allodynia in mice was assessed using the von Frey test. Quantitative real-time PCR (qRT-PCR), Western blotting and enzyme-linked immunosorbent assay (ELISA) were performed to evaluate the expression of CBLN2. Immunofluorescence was used to determine CBLN2’s cellular localization. DNA methylation of Cbln2’s promoter region was examined using methylation-specific PCR (MSP) and bisulfite sequencing PCR (BSP). Neuronal excitability was assessed through whole-cell patch-clamp recordings. Results Integration of cross-species single-nucleus RNA sequencing (snRNA-seq) datasets identified dominant CBLN2 expression in Aδ, Aβ and c-fiber low-threshold mechanoreceptors (LTMRs), with significant upregulation observed in a murine model of inflammatory migraine. Consistently, CBLN2 expression was upregulated in the TG of pIONT-induced TNP mice and localized to neurons with myelinated axons, peptidergic and nonpeptidergic nociceptors. siRNA-mediated Cbln2 knockdown attenuated mechanical allodynia, confirming its role in pain initiation and maintenance. Notably, Cbln2 expression was partially dependent on promoter demethylation. MSP and BSP analyses revealed significantly reduced methylation of the Cbln2 promoter in pIONT mice compared to sham controls. Furthermore, pIONT induced persistent upregulation of ten-eleven translocation 3 (TET3) in the TG, while Tet3 knockdown alleviated neuropathic pain and downregulated both Tet3 and Cbln2 expression. Additionally, exogenous CBLN2 potentiated neuronal excitability and activated extracellular signal-regulated kinase (ERK) signaling. Inhibition of the mitogen-activated protein kinase (MAPK)/ERK kinase (MEK) pathway abolished CBLN2-induced hypersensitivity and suppressed the expression of proinflammatory cytokines, including Cxcl1, Cxcr2, Cxcl9, Cxcl10, and Il-6. Conclusions TET3-mediated demethylation of the Cbln2 promoter drives ERK-dependent neuronal hyperexcitability and neuroinflammation following pIONT. The dual regulatory effects on neuroinflammatory cascades establish CBLN2 as a novel therapeutic target for the treatment of TNP.